2013
DOI: 10.1590/s0034-8910.2013047004753
|View full text |Cite
|
Sign up to set email alerts
|

Infection and childhood leukemia: review of evidence

Abstract: OBJECTIVETo analyze studies that evaluated the role of infections as well as indirect measures of exposure to infection in the risk of childhood leukemia, particularly acute lymphoblastic leukemia.METHODSA search in Medline, Lilacs, and SciELO scientific publication databases initially using the descriptors "childhood leukemia" and "infection" and later searching for the words "childhood leukemia" and "maternal infection or disease" or "breastfeeding" or "daycare attendance" or "vaccination" resulted in 62 pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
0
7
0
2
Order By: Relevance
“…As in previous reviews, there continues to be substantial heterogeneity among the studies; however, our review focuses on specific objectives and highlights the recent developments of the field (McNally and Eden, 2004; Buffler et al , 2005; Greaves, 2006; Ma et al , 2009; Maia Rda and Wunsch Filho, 2013). There are several limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous reviews, there continues to be substantial heterogeneity among the studies; however, our review focuses on specific objectives and highlights the recent developments of the field (McNally and Eden, 2004; Buffler et al , 2005; Greaves, 2006; Ma et al , 2009; Maia Rda and Wunsch Filho, 2013). There are several limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods for measuring infections such as using administrative data overcome these limitations, but may lack information on important confounders. Other than narrative summaries (McNally and Eden, 2004; Buffler et al , 2005; Ma et al , 2009; Maia Rda and Wunsch Filho, 2013), no study has attempted to synthesise and quantitatively pool studies examining the relationship using a history of infections, or tried to explain the differences between the studies. The aim of this systematic review and meta-analysis was to assess the relationship between childhood infections, and the development childhood ALL by summarising the findings for an overall measure of infections, the frequency, severity, timing of infections, and examining specific infectious agents and syndromes.…”
mentioning
confidence: 99%
“…The overhygienization is becoming increasingly widespread in modern world, and it is believed to cause increased antibiotic resistance and permanently increasing number of persons with weakened immunity in developed societies ( Bloomfield et al, 2016 ). Although lack of microbial exposure may not be the only causal factor, the assumptions of this hypothesis have been repeatedly confirmed through both observational and experimental studies ( Maia Rda and Wünsch Filho, 2013 ). Under-using of immune system early in life can likely cause not only atopic conditions, but also autoimmune states ( Kramer et al, 2013 ).…”
Section: Hypothetical Considerationsmentioning
confidence: 93%
“…Exposure to animals in early childhood has been associated with decreased development of allergies (Campo et al 2006; Ownby et al 2002) and allergies have been inversely associated with leukemia risk in children and adults (Linabery et al 2010; Nanni et al 1996; Schuz et al 2003; t Mannetje et al 2012). Additionally, maternal infections during pregnancy or early life infections in children have been positively associated with childhood leukemia in some studies (Maia Rda and Wunsch Filho 2013). Studies have shown that infection with viruses found in animals, such as avian sarcoma virus (Copeland et al 1975), oncornaviruses, papovaviruses, and adenoviruses (Swenberg 1977) can lead to the development of brain tumors in animals.…”
Section: Discussionmentioning
confidence: 99%